2014
DOI: 10.1109/tmi.2013.2279994
|View full text |Cite
|
Sign up to set email alerts
|

Unmixing Molecular Agents From Absorbing Tissue in Multispectral Optoacoustic Tomography

Abstract: Detection of intrinsic or extrinsically administered chromophores and photo-absorbing nanoparticles has been achieved by multi-spectral optoacoustic tomography (MSOT). The detection sensitivity of MSOT depends not only on the signal to noise ratio considerations, as in conventional optoacoustic (photoacoustic) tomography implementations, but also on the ability to resolve the molecular targets of interest from the absorbing tissue background by means of spectral unmixing or sub-pixel detection methods. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
165
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(166 citation statements)
references
References 54 publications
1
165
0
Order By: Relevance
“…39 To quantify the signal, the mean pixel intensities (MPIs) of the signal were extracted from each region (eyes and neck lymph nodes of both sides) using the linear regressionprocessed images. 40 Photoacoustic images were spectrally unmixed with the linear regression algorithm of the native software, with the same 25 lM QC-1 spectrum as well as oxyhemoglobin and deoxyhemoglobin selected as input spectra. Details of the photoacoustic image analysis are provided in Supplementary Material B.…”
Section: Signal Visualization and Quantificationmentioning
confidence: 99%
“…39 To quantify the signal, the mean pixel intensities (MPIs) of the signal were extracted from each region (eyes and neck lymph nodes of both sides) using the linear regressionprocessed images. 40 Photoacoustic images were spectrally unmixed with the linear regression algorithm of the native software, with the same 25 lM QC-1 spectrum as well as oxyhemoglobin and deoxyhemoglobin selected as input spectra. Details of the photoacoustic image analysis are provided in Supplementary Material B.…”
Section: Signal Visualization and Quantificationmentioning
confidence: 99%
“…The in vitro and in vivo optoacoustic spectra derived from the phantom measurements and in vivo appear similar to each other but not identical. The differences might be attributed to the sparse spatial sampling applied in vivo and possibly spectral alterations due to the wavelength-dependent light fluence distribution (24). Similarly to the observations in Figure 2, Figure 4A also shows a discrepancy between the absorption spectrum measured by a spectrophotometer and the optoacoustic measurements.…”
Section: Detection Of Sinc In Murine Subcutaneous Tumor Modelmentioning
confidence: 54%
“…Imaging of lung cancer and noninvasive imaging of brain tumors in humans appears unlikely to work without at least severe degradation of image quality. Quantification of absorber concentrations in optoacoustic images is considered an unsolved problem, because the wavelength-dependence of light attenuation in tissue distorts the measured optoacoustic spectrum for deep-lying sources (18,91). With time, optoacoustic imaging systems are likely to become more robust and user-friendly as the technology becomes more established.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that excitation at multiple optical wavelengths, combined with a statistical subpixel detection method (adaptive matched filter-AMF) for spectral unmixing (18), can effectively enhance the sensitivity over single wavelength optoacoustic imaging on the order of 14 to 40 times in molecular imaging applications (19). This performance is summarized in Fig.…”
Section: Advances In Multispectral Detection and Sensitivity Improvemmentioning
confidence: 99%
See 1 more Smart Citation